2021
DOI: 10.1097/aud.0000000000001145
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Implant Compression Optimization for Musical Sound Quality in MED-EL Users

Abstract: Objectives: Variations in loudness are a fundamental component of the music listening experience. Cochlear implant (CI) processing, including amplitude compression, and a degraded auditory system may further degrade these loudness cues and decrease the enjoyment of music listening. This study aimed to identify optimal CI sound processor compression settings to improve music sound quality for CI users.Design: Fourteen adult MED-EL CI recipients participated (Experiment No. 1: n = 17 ears; Experiment No. 2: n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…This result might have been caused by the strong compression applied to the music by the sound coding strategy and the much narrower EDR available for CI users in applied to recorded comparison to the perceivable DR in NH listeners. Gilbert et al (2022) showed that CI users prefer less compression (allocate more EDR) to the softer passages (below the knee point) and be more compressive for louder (above the knee point) parts of music with respect to the clinical compression system. Results of our study show the efficacy and importance of a back-end compression for music in the Crystalis sound coding strategy.…”
Section: Discussionmentioning
confidence: 99%
“…This result might have been caused by the strong compression applied to the music by the sound coding strategy and the much narrower EDR available for CI users in applied to recorded comparison to the perceivable DR in NH listeners. Gilbert et al (2022) showed that CI users prefer less compression (allocate more EDR) to the softer passages (below the knee point) and be more compressive for louder (above the knee point) parts of music with respect to the clinical compression system. Results of our study show the efficacy and importance of a back-end compression for music in the Crystalis sound coding strategy.…”
Section: Discussionmentioning
confidence: 99%
“…There are very few systematic studies exploring the effect on music perception of varying the compression threshold or the compression ratio of the front-end AGC in a CI. Gilbert et al (2021) explored the effect of varying the compression ratio of the front-end AGC in the Med-El CI, keeping the compression threshold fixed at 48 dB SPL, and found no significant effect on music preferences. However, they varied the compression ratio only over a small range (2.5 to 3.5) and they used samples of music with a single fixed input level of 65 dBA.…”
Section: Squeezing Music Into the Limited Dynamic Range Of The CI Usermentioning
confidence: 99%
“…Although speech understanding remains possible despite significant impairment in spectral and temporal cues, the same limitation can significantly affect CI users' ability to appreciate and recognize music, including melody and timbre (16,17). Although different sound processing strategies, current routing techniques, stimulation modes, and DR compression have been used in studies to optimize CI fitting for music and speech perception (18)(19)(20)(21), the effect of different CI programming methods has not been investigated. Therefore, the first aim of the study was to investigate the effect of two different programming methods on CI users' speech perception, spectral-temporal resolution, and music perception, the objective eSRT-based program and the behaviorally based program with LB.…”
Section: Introductionmentioning
confidence: 99%